TREATMENT OUTCOMES OF CLOSED INTERLOCKING INTRAMEDULLARY NAILING FOR DIAPHYSEAL FRACTURES OF BOTH LEG BONES AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the surgical outcomes of closed intramedullary interlocking nailing in the treatment of diaphyseal fractures of both bones of the leg.Subjects and methods: A retrospective descriptive study was conducted on 60 patients with tibial or both-bone leg shaft fractures who underwent closed intramedullary interlocking nailing at Viet Duc University Hospital between May 2024 and April 2025.Results: The mean age of the patients was 42.8 ± 16.0 years, with a predominance of males (55%). The most common clinical manifestations were localized tenderness (100%), loss of lower limb function (95%), and limb deformity (81.7%). According to the AO classification, type B2 fractures accounted for the highest proportion (48.3%). Regarding surgical outcomes, the mean operative time was 53.4 ± 18.6 minutes. Postoperatively, 100% of cases showed primary wound healing, and all intramedullary nails and locking screws were in correct alignment on radiographs. The reduction quality was rated as good or excellent in 100% of cases. For bone union, 95% of patients achieved excellent consolidation, 1.7% fair, and 3.3% poor results. At 6 months postoperatively, over 90% of patients attained excellent or good functional recovery, while 3.3% had fair and 5% poor outcomes. The overall complication rate was 6,7%, including nonunion (3.3%), lateral malleolar ulceration (1.7%), and delayed union (1.7%).Conclusion: Closed interlocking intramedullary nailing provides excellent surgical and functional outcomes and remains the treatment of choice for diaphyseal closed fractures of the tibia in current clinical practice.
Keywords: Tibial and fibular shaft fractures, interlocking intramedullary nailing.